Event Management Analysis of Student Sports - Dicky Hendrawan; Eka Abdurrahman; Agung Nugroho; Sipayung, Dinni Khairiah (Journal Management of Sport, 2022)
The purpose of this research is to find out the planning of the Student Sports Event (PORMA) event from the beginning of planning to the end of the event and to find out the function of the role of public relations at the PORMA event. This research uses a qualitative approach with descriptive research. The results of this study are: 1) Research, where the PORMA committee made observations through digital media related to things that were going viral; 2) Design, basically with a design that attracts mass attention, the PORMA committee uses the brainstorming and mindmapping stages to be able to attract the attention of participants; 3) Planning, the PORMA committee also prepares the event design according to their template that has been made before starting the tournament by holding a Technical Meeting, and this e-sports tournament is planning B of the PORMA event; 4) Coordination of the committee, participants, sponsors, and media partners by using social media in the form of Whatsapp and Zoom Meeting. 5) Evaluation of, the PORMA event to get a positive response from participants. Then the committee evaluated themselves at the PORMA event so that the mistakes and shortcomings that occurred yesterday would not be repeated at the next PORMA.